Peran Budaya Perusahaan Dalam Meningkatkan Inovasi Dan Kreativitas Karyawan - Ardiansyah, Feri; Mukti Ardiansyah, Wahyu; Zein Saleh, Mohamad (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
In the era of globalization and increasingly fierce business competition, innovation and creativity have become critical factors for the sustainability and growth of organizations. This study aims to analyze the impact of corporate culture on the level of innovation and creativity within organizations. Using a qualitative descriptive approach with secondary data analysis, this research focuses on literature from books, journals, and other publications related to innovation culture. The findings reveal that corporate culture plays a crucial role in enhancing employee innovation and creativity. A corporate culture that supports collaboration, openness, recognition of new ideas, and flexibility significantly influences employees' ability to innovate and think creatively. However, the implementation of an innovative culture faces challenges such as resistance to change, lack of resources, and entrenched organizational norms. This study provides practical implications for management, suggesting the creation of a collaborative work environment, implementation of reward systems, open communication, and flexibility in work processes to foster innovation and creativity. Further research is recommended to explore how specific elements of corporate culture can be optimized, particularly in the context of Indonesia.